2018
DOI: 10.1111/jfpe.12678
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the linear growth velocity on the properties of sucrose crystals produced from mixed syrups

Abstract: The systematic study presented addresses the need to understand the co‐crystallization of beet and cane material better. This is important because of the sugar market liberalization in 2017. Here the effect of crystal growth velocity on final sugar quality is investigated. Comparing three different thermal setups, studying different cane and beet mixtures color inclusion into sucrose crystals was analyzed. Within one thermal setup supersaturation was practically constant. Almost exclusively the time necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In order to evaluate the initial qualitative characteristics of various crystallizing agents, they were analyzed dispersedly and it was found that the size of the crystals affects the rate of formation and uniformity of sugar crystals (Schlumbach et al, 2018;Srisanga et al, 2015;Zinab et al, 2015). Results obtained are displayed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the initial qualitative characteristics of various crystallizing agents, they were analyzed dispersedly and it was found that the size of the crystals affects the rate of formation and uniformity of sugar crystals (Schlumbach et al, 2018;Srisanga et al, 2015;Zinab et al, 2015). Results obtained are displayed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%